Dental hygiene practices and the pattern of dental caries in preschool children in Ragama - Perera, P.; Abeweera, N.; Fernanado, M.; warnakulasuria, T.W.; Ranathunga, N. (Sri Lanka Medical Association, 2012)
INTRODUCTION: Dental caries is a common problem among preschool children, but often neglected as deciduas teeth are replaced later by permanent teeth. However, for many reasons, protecting deciduas teeth is very important. AIMS: The objectives of this study were to describe the prevalence of dental caries among preschool children and assess the utilization of dental care facilities. METHODS: A descriptive cross sectional study was done between August 2010 and October 2010 at child welfare clinics held in the Ragama MOH area. Consecutive children aged between 2 and 5 years attending the clinics were recruited with the consent of parents. An interviewer administered questionnaire was used to obtain data and the mouth was examined for caries. Total decayed-missing-filled (dmft) score and significant caries index (SIC) were calculated to describe the prevalence of dental caries. Care index was calculated to describe the use of dental services. RESULTS: Out of 410 children recruited, none had routine visits to a dentist. Though practices related to brushing teeth were satisfactory, 37.8% children in the study sample had caries. This increased to 68.8% by 5 years of age. Mean dmft score for the whole sample was 1.41 and SIC index was 4.09. The Care index was 4.72. The dmft score in girls was higher than boys. Incisors of the upper jaw were the mainly affected teeth. CONCLUSIONS: Prevalence of dental carries among this cohort of Sri Lankan preschool children is very high. The level of dental care for preschool children at present appears to be unsatisfactory.
Poster Presentation Abstract (PP 05), 125th Anniversary Scientific Medical Congress, Sri Lanka Medical Association, June 2012 Colombo, Sri Lanka
Keywords: Dental hygiene practices